Preparing STEM teachers : the UTeach replication model - Goodell, Joanne E.; Koç, Selma (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"STEM project-based instruction is a pedagogical approach that is gaining popularity across the USA. However, there are very few teacher education programs that focus specifically on preparing graduates to teach in project-based environments. This book is focused on the Uteach program, a STEM teacher education model that is being implemented across the USA in 45 universities. Originally focused only on mathematics and science, many UTeach programs are now offering engineering and computer science licensure programs as well. This book will provide a forum to disseminate how different institutions have implemented the UTeach model in their local context. Topics discussed will include sustainability features of the model, and how program assessment, innovative instructional programming, classroom research and effectiveness research have contributed to its success. The objectives of the book will be: To help educators gain insight into a teacher education organizational model focused on STEM and how and why it was developed To present the theoretical underpinnings of a STEM education model, i.e. deep learning, conceptual understanding To present innovative instructional programming in teacher education, i.e. project-based instruction, functions and modeling, research methods To present research and practice in classroom and field implementation and future research recommendations To disseminate program assessments and improvement efforts"--